Ultrafast Flash Energy Conductance at MXene‐Surfactant Interface and Its Molecular Origins. Issue 23 (14th October 2019) - Li, Jiebo; Zhang, Qi; Yan, Li; Wu, Guorong; Hu, Mingjun; Lin, Xubo; Yuan, Kaijun; Yang, Xueming
Abstract: With the developments of energy science, biomedical therapy, and electronic technology, interfacial thermal transport has become a key issue for many applications. Furthermore, with the growing importance of thermal utilization of new 2D material MXene, capturing the interfacial thermal conduction of MXene‐soft material in solution is an urgent task. In this work, transient absorption dynamics is employed to investigate MXene (Ti3 C2 Tx )‐surfactant interfacial energy conductance in water solution. The sodium dodecyl sulfate molecules could not directly interact with Ti3 C2 Tx surface, and thus failed to inhibit the interfacial heat transfer of Ti3 C2 Tx . To the opposite, attributed to strong coulomb interaction, cetrimonium bromide (CTAB) molecules could form bilayers on Ti3 C2 Tx to isolate the energy dissipation from Ti3 C2 Tx to water and thus alter the heat dissipation rates of Ti3 C2 Tx . The interfacial energy conductance G ≈81 MW m −2 K −1 between CTAB and Ti3 C2 Tx is quantitatively obtained. Molecular dynamics simulation also presented the flash heating could disrupt the bilayer structures, showing that the finding contributed to the future engineering design for MXene thermal applications through tuning the attaching layer at MXene interface. Abstract : This work employs transient absorption dynamics to investigate MXene (Ti3 C2 Tx )‐surfactant interfacial energy conductance in water solution. Attributed to strong coulomb interaction, CTAB molecules could form bilayers on Ti3 C2 Tx to isolate the energy dissipation from Ti3 C2 Tx to water and thus alter the heat dissipation rates of Ti3 C2 Tx with the interfacial energy conductance G ≈81 MW m −2 K −1 .